2022
DOI: 10.5999/aps.2021.01396
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of fistula after primary cleft palate repair: a 25-year assessment of one surgeon’s experience

Abstract: Background Cleft lip and cleft palate are the most frequent congenital craniofacial deformities, with an incidence of approximately 1 per 700 people. Postoperative palatal fistula is one of the most significant long-term complications. This study investigated the incidence of postoperative palatal fistula and its predictive factors based on 25 years of experience at our hospital.Methods We retrospectively reviewed 636 consecutive palatal repairs performed between January 1996 and October 2020 by a single surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…30 The staging and techniques used in the primary palatoplasty have been demonstrated to be correlated to incidence of postoperative fistula. 30,31 Some studies have also pointed to an older age at time of primary palate repair to be protective for oronasal fistula. 30 However, others have found no difference in the incidence of post-operative ONF based on age at operation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…30 The staging and techniques used in the primary palatoplasty have been demonstrated to be correlated to incidence of postoperative fistula. 30,31 Some studies have also pointed to an older age at time of primary palate repair to be protective for oronasal fistula. 30 However, others have found no difference in the incidence of post-operative ONF based on age at operation.…”
Section: Discussionmentioning
confidence: 99%
“…30 However, others have found no difference in the incidence of post-operative ONF based on age at operation. [31][32][33] Nationally, the secondary palatoplasties presumed to be addressing fistulas had an average age of 6.85 ± 4.65 years, which was earlier than those performed for VPI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…type of study Park MS et al, 8 retrospective Sumun K et al, 9 retrospective Jung SE et al, 10 retrospective Mantilla-Rivas et al, 11 retrospective Shaffer AD et al, 12 retrospective Yang CH et al, 13 retrospective Bruneel L et al, 14 retrospective Imbery TE et al, 15 retrospective Kim E et al, 16 retrospective Ha S et al, 17 retrospective Annigeri VM et al, 18 retopective Kobayashi H et al, 5 retopective 16 , as they reported that after adjustment for potential confounders with multivariate analysis, patients who received four or more sets of VTs, those with a history of TM perforation, and those with isolated cleft palate were found to be at an increased risk for hearing loss at 10-year follow-up. Age of first tube placement and total number of otologic complications were not independent predictors of hearing loss on adjusted analysis.…”
Section: Authormentioning
confidence: 99%